Investigation of 22Mg levels via resonant scattering of 18Ne + α - Cha, S. M.; Chae, K. Y.; Abe, K.; Bae, S.; Binh, D. N.; Choi, S. H.; Duy, N. N.; Ge, Z.; Hahn, K. I.; Hayakawa, S.; Hong, B.; Iwasa, N.; et al. (Frontiers in Physics, 2023)
The α resonant scattering on 18Ne was measured in inverse kinematics to understand the α-clustering of proton-rich 22Mg nucleus. The measurement was performed at the CNS RadioIsotope Beam Separator (CRIB) of Center for Nuclear Study, the University of Tokyo, located at the RIBF of RIKEN Nishina Center. The excitation function of 22Mg was obtained for the excitation energies of 10–16 MeV by adopting the thick target method. Several resonances were evident in the present work, which implies the existence of energy levels with large α widths. Since energy levels were not clearly observed at the astrophysically important energy range, upper limits on the 18Ne(α, α)18Ne cross section were set. The astrophysical impact was also investigated by estimating the 18Ne(α, p)21Na cross section.